Development of E-Module Using Book Creator Application on Writing Material: A Development of Digital Teaching Material at Elementary School - Hani Atus Sholikhah; Khalidatun Nuzula; Novritika; Nandang Heryana; Tita Ratna Wulan Dari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Research This aims to develop material learning in the form of e-modul assisted by the book creator application on writing material for grade 6 elementary school students. Type study This use study and development or R&D (Researchand Development) modification based on a combination of Borg & Gall and Aleesi & Trollip. Stages of research on the development of e-modules based on the Book Creator application on this writing material includes: (1) Introduction Study(Borg & Gall); (2) Planning ( Planning Allies & Trollip); (3) Design (Design Allesi & Trollip); (4) Analysis of teacher need and student; and (5) expert validation. The data that analyzed in this study are quantitative and qualitative data. Quantitative data in the form of data from questionnaire, while qualitative data in the form of interviews and observation.The data sources in this study were 150 students and 30 teachers who took English lessons. Indonesia in grade 6 at 15 elementary schools/Islamic elementary schools throughout South Sumatra . The data were analyzed qualitatively and quantitatively. Quantitative data analysis was carried out by calculating the average value of the Likert scale for each statement, then interpreted in relation to the tendency of respondents (teachers and students, and validators) on the choices. Qualitative data analysis used coding, in the form of open responses into the same theme or category according to the criteria , involving expert validation, limited trials, and data triangulation. The results of this study indicate that 28% student state very need , 42% need , 22% No need , And 8% very No need . Analysis of teacher needs shows that 58% of teachers stated that they really needed it , 42% need , 0% no need , and 0% very unnecessary . The validation results show that the percentage of language validation results with a score of 88 (very valid), material validation with a score of 90 (very valid), and media validation with a score of 90 (very valid). The conclusion of the validation analysis results is very valid with an average of 89 (very valid) . The practicality test shows that the average product is in the very practical category with a score of 89. This study concludes that e-module teaching materials assisted by the book creator application on writing material are suitable for use in elementary school.